Relations in the tourism supply chain - E. Jaremen, Daria; Nawrocka, Elżbieta (Management and Administration Journal, 2023)
The critical review of publications in the field of economics and management allows one to state that research covering the tourism supply chain (TSC) is quite limited and non-exhaustive. The article presents the review of the most significant studies discussing the problems of the tourism supply chain. The authors attempted to indicate gaps in the existing models of the tourism supply chain and on that basis suggested their own model emphasizing, in particular, the relations occurring between its components. It takes into account additional elements, which have not been included so far, i.e. the complex and service oriented nature of a tourist product and its close relations with space, immobility of supply and mobility of demand, as well as the network structure of the tourism economy based on new technologies in terms of information and communication.